Gallograeci and elephants at Megara - Panovski, Stefan (Živa Antika / Antiquité Vivante, 2015)
The aim of this paper is to re-examine the arguments concerning the question whether Antiochos I did indeed send military aid to Antigonos Gonatas during the Chremonidean War. The assumption rests on three pieces of evidence - the inscription of Brikkon, the elephants at Megara and the presence of Celtic troops from Gallograecia. Since it has been proven long ago that the inscription of Brikkon has been misunderstood and is from a later date, there is nothing more to be added in this instance. As for the elephants, the argument is far less convincing once it is realized that in the years prior to the Chremonidean War Antigonos already had some in his army, and therefore there is no need to assume that the ones he deployed at Megara were sent from Antiochos I. The argument becomes even less persuasive if we take into account that the situation in Asia Minor was far less settled than once thought, and especially since there are some indications that at the time Antiochos did not even had a huge number of elephants in his army and consequently seems doubtful whether he would have been ready to further weaken his elephant corps by sending some of them to Antigonos. Similarly, the mention of troops from Gallograecia, though convincing at first glance, is far less persuasive on closer examination. Considering the problems with Justin’s description, his authority without the support of the other two arguments should not be accepted at face value. On top of that, since on another occasion he uses the name to denote not the Celts from Asia Minor but from the Balkans, the possibility that we are dealing with Celts from the Balkans can not be ruled out. In conclusion, though nothing can be said with absolute certainty, until some new evidence emerges, there is not a single compelling argument that Antiochos took part in the Chremonidean War.